“Unspoken Affection”: Articulating Friendship in Gladys Ng’s The Pursuit of a Happy Human Life - Foo, Carissa (SARE: Southeast Asian Review of English, 2020)
Gladys Ng’s The Pursuit of a Happy Human Life (2016) has been described as a short film about the “unspoken affection and awkward conversations [that] fill the last day two best friends [Yokes and Steph] spend together.” Inasmuch as it is about goodbyes, it is also about the many ways to not say goodbye. Yokes pauses, digresses, and acts out, refusing to bid farewell to Steph who is leaving Singapore. Their friendship is characterised by an inexpression which is product of adolescence and discipline, as well as a strategy to circumvent normative practices of friendship. Drawing on the philosophies of Deleuze and Bergson, this article attempts to evince the unspoken affections through the acts of hesitating and acting out. With a discussion on friendship dynamics that are contingent on a renewed understanding of what it means to hesitate and act out, the article will frame inexpression as a strategic aporia, in which the lack of certainty and ineloquence enables a reconceptualisation of friendship. That is, inexpression becomes a means of reaching out, beyond the body and frame, to present a corporal assemblage in which meaning is no longer localised but dispersed, as if the characters are befriending the audience.